2023
DOI: 10.1155/2023/9708282
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of the Prognostic Role of Genes Related to Lipid Metabolism in Head and Neck Squamous Cell Carcinoma

Abstract: Head and neck squamous cell carcinoma (HNSCC) has become a prevalent malignancy, and its incidence and mortality rate are increasing worldwide. Accumulating evidence has indicated that lipid metabolism-related genes (LMRGs) are involved in the occurrence and development of HNSCC. This study investigated the latent association of lipid metabolism with HNSCC and established a prognostic signature based on LMRGs. A prognostic risk model composed of eight differentially expressed LMRGs (PHYH, CYP4F8, INMT, ELOVL6,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…Consistent with our study, higher expression of PHYH is associated with better prognosis in head and neck squamous cell carcinoma (HNSCC) and renal clear cell carcinoma (CCRCC). [41][42][43] Additionally, PHYH is highly expressed in ischemia-reperfusion injury (IRI) and holds potential as a diagnostic biomarker for IRI. 44 In our study, we observed that higher expression of PHYH in nontumor tissues of HCC patients correlated with better prognosis.…”
mentioning
confidence: 99%
“…Consistent with our study, higher expression of PHYH is associated with better prognosis in head and neck squamous cell carcinoma (HNSCC) and renal clear cell carcinoma (CCRCC). [41][42][43] Additionally, PHYH is highly expressed in ischemia-reperfusion injury (IRI) and holds potential as a diagnostic biomarker for IRI. 44 In our study, we observed that higher expression of PHYH in nontumor tissues of HCC patients correlated with better prognosis.…”
mentioning
confidence: 99%